Current status of pathogen handling in European laboratories: focus on viral inactivation process - Pastorino, Boris; Touret, Franck; Gilles, Magali; De Lamballerie, Xavier; Charrel, Remi N. (Frontiers in Bioengineering and Biotechnology, 2024)
For handling safely infectious agents, European laboratories must comply with specific EC Directives, national regulations and recommendations from the World Health Organization (WHO). To prevent laboratory acquired infections (LAIs) and pathogens dissemination, a key biosafety rule requires that any infectious material (clinical specimens or research samples) manipulated outside a biosafety cabinet (BSC) must be inactivated unless the lack of infectivity is proven. This inactivation process is a crucial step for biosafety and must be guided by a rigorous experimental qualification and validation procedure. However, for diagnostic or research laboratories, this process is not harmonized with common standard operation procedures (SOPs) but based on individual risk assessment and general international guidelines which can pose problems in emergency situations such as major outbreaks or pandemics. This review focuses on viral inactivation method, outlining the current regulatory framework, its limitations and a number of ways in which biosafety can be improved.